Историја на македoнското државно знаме - History of the Macedonian National Flag - Jovan Jonovski (Македонски хералд - Macedonian Herald, 2022)
The first recorded flag usage in Byzantine Macedonia goes back to the 10th century. Portolans shows a yellow flag with a red double-headed eagle above City od Skopje. The heraldic flags attributed to Alexander the Great in medieval European sources are also included. Among the rebellion flags under Ottoman Empire the oldest preserved is from 1876 Macedonian Uprising in Razlovci. From the insurgent flags of Ilinden Uprising in 1903 came the color of the flag on Macedonian national flag of 1943. Тhe red partisan five-pointed star is from 1941 and latter appears on the flags of all republics in Yugosalvia. Under this flag the Republic of Macedonia won its independence in 1991. The star was replaced in 1992 with the yellow 16-pointed sun of Kutlesh/Vergina type, which in turn was replaced with an 8-rayed divergent sun. The design processes and proposals are discussed in detail.